Changing prognosis of childhood cancer--an overview. - Lin, H.P. (1993)
Significant advances in diagnosis and management have cured the majority of children with cancer. In the leukaemias, the commonest childhood malignancy, intensive induction-consolidation is important to ensure a lasting cure in about 65-80% and to eliminate the traditionally bad prognostic risk factors associated with less intensive treatment. Bone marrow transplantation (BMT) has a curative role in the minority who relapse particularly while on treatment. With few exceptions, most paediatric solid tumours are curable. Although the multimodal approach is responsible for the progress made, chemotherapy has emerged to play a dominant role. It has, in several tumours, obviated or reduced the need for radiotherapy and/or surgery. In Wilms' tumour and Hodgkin's disease, refinement of treatment is now in progress to reduce therapy-related morbidity while not sacrificing efficacy.